2019
DOI: 10.1155/2019/1574749
|View full text |Cite
|
Sign up to set email alerts
|

Smart Detection: An Online Approach for DoS/DDoS Attack Detection Using Machine Learning

Abstract: Users and Internet service providers (ISPs) are constantly affected by denial-of-service (DoS) attacks. This cyber threat continues to grow even with the development of new protection technologies. Developing mechanisms to detect this threat is a current challenge in network security. This article presents a machine learning- (ML-) based DoS detection system. The proposed approach makes inferences based on signatures previously extracted from samples of network traffic. The experiments were performed using fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(98 citation statements)
references
References 39 publications
2
92
0
4
Order By: Relevance
“…To overcome this problem we need to tune these algorithms more using other datasets with different attack scenarios. Comparing our results to other solutions that are using the CIC-DDoS2019 dataset such as [46,47], we can see that our results are among higher values with a percentage over 90 and in some cases even higher. But comparing our results with some other research results is not valid in our case, because we have shown here if we have any three algorithms, whether they are giving better or worse results, we are going to get better results than each of them individually.…”
Section: Discussionmentioning
confidence: 56%
“…To overcome this problem we need to tune these algorithms more using other datasets with different attack scenarios. Comparing our results to other solutions that are using the CIC-DDoS2019 dataset such as [46,47], we can see that our results are among higher values with a percentage over 90 and in some cases even higher. But comparing our results with some other research results is not valid in our case, because we have shown here if we have any three algorithms, whether they are giving better or worse results, we are going to get better results than each of them individually.…”
Section: Discussionmentioning
confidence: 56%
“…Accuracy (Acc), detection rate (DR) and false alarm rate (FAR) are the assessed metrics. Detailed explanation about these metrics can be found in [6].…”
Section: A Resultsmentioning
confidence: 99%
“…, M mb . If the (R + 1)-th mode unfolding matrices in (6) are represented as a function of its rows and replace the Hadamard product by the dot product, such equation can be rewritten as…”
Section: B Proposed Mlp Architecturementioning
confidence: 99%
“…Hosseini and Azizi [ 13 ] proposed a hybrid framework based on a data stream approach for DDoS attack detection where the computational load is divided between the client and proxy side. Next, Lima Filho et al [ 14 ] proposed a random forest-based DDoS detection system in which several volumetric attacks, such as Transmission Control Protocol (TCP) flood, User Datagram Protocol (UDP) flood, and Hyper Text Transfer Protocol (HTTP) flood, are early identified. Finally, Wang et al [ 6 ] proposed a method for detecting DDoS attacks in which the optimal features are obtained by combining feature selection and multilayer perceptron (MLP) classification algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…Such a matrix is forwarded to the ML classification algorithm for classification tasks, where the predicted class label vector is computed. Since decision tree, random forest and gradient boosting algorithms present considerable results in network intrusion detection problems, they are adopted in this paper for classifying the network traffic data [ 14 ].…”
Section: Proposed Average Common Feature Extraction Technique For mentioning
confidence: 99%